Fatty acid composition of Agaricus bisporus fruit bodies - Burda, Nadiia; Zhuravel, Iryna; Orlenko, Inna; Hutsol, Viktoriia (Annals of Mechnikov's Institute, 2023)
Introduction. Agaricus bisporus (J. Lange) Pil.) is a mushroom of the Agaricus family (Agaricaceae), which is cultivated as an edible mushroom. According to the literature, Agaricus bisporus contain beta-glucans, sterols (ergosterol), ergothioneine, vitamins of groups B, D and C, phenolic compounds, in particular flavonoids and phenolic acids, dietary fibers (chitin), amino acids, including essential fatty acids (linoleic, linolenic), proteins, mineral elements (zinc, selenium, magnesium, iron, potassium, sodium, calcium, phosphorus, sulfur, manganese). Since this mushroom is widely used in food, studies of the content of proteins, fats, and mineral elements in fresh and preserved samples of raw materials were conducted from the point of view of nutraceutical approaches. Scientists from Pakistan found that among the detected fatty acids in the fruit bodies of Agaricus bisporus, linoleic acid prevailed in content (44.19%), and in another type of mushroom, Agaricus bitorquis (Quél.) Sacc., oleic acid dominated (40.13%). According to Turkish scientists who also studied the fatty acid composition of Agaricus bisporus, linoleic acid prevailed among all fatty acids (53.45 - 68.78%). Palmitic, oleic, and stearic acids were identified among other acids that also had significant quantitative content. Information about the dominance of linoleic acid among fatty acids is confirmed in the works of other scientists. It should be noted that the chemical composition of mushrooms can be variable and depend on growing conditions. Agaricus bisporus is also being studied as a raw material that has pronounced pharmacological activity. It has been established that the fruit bodies of Agaricus bisporus have antioxidant, antibacterial, anti-inflammatory, antitumor and immunomodulatory effects. In view of the powerful potential of the use of Agaricus bisporus in pharmacy and for a more in-depth understanding of its nutritional value, it is appropriate to conduct further phytochemical studies. The aim of the work was to study the fatty acid composition of Agaricus bisporus fruit bodies. Materials and methods. To carry out the experiment, the fruiting bodies of Agaricus bisporus were purchased from the company "ChP Mykhaylovsky A.V." (Ukraine). Dried raw materials were used for the experiment. Fatty acids were revealed in the form of their methyl esters. Fatty acid methyl esters were studied at Selmichrome-1 gas chromatograph with a flame ionization detector. Stainless steel gas chromatography column, 2,5 meters long and 4 mm internal diameter, was filled with stationary phase – inerton treated with 10% diethyleneglycol succinate (DEGS). Chromatograph operation parameters: column thermostat temperature – 180°С, vaporizer temperature – 230°С, detector temperature – 220°С, carrier gas (nitrogen) flowrate – 30 cm3/min, sample 2 mm3 acids methyl esters solution in hexane. Fatty acid methyl esters were indentified by retention time of fatty acid methyl esters peak standard samples as compared to standard mixture. Reference samples were Merck standards of saturated and unsaturated fatty acid methyl esters. Composition of methyl esters was calculated by internal normalzation method. Fatty acid methyl esters were obtained by modified Peisker method to ensure total methylation of fatty acids. For methylation a 100:100:1 mixture of chloroform with methanol and sulfuric acid was used. 30-50 µl lipophilic fraction was measured to glass ampoules, 2,5 ml methylating mix added and ampoules were sealed. Then they were introduced to thermostat at 105°С for 3 hours. After methylation the ampoules were opened, their contents transferred to a beaker, zink sulfate added on lancet tip, 2 ml purified water and 2 ml hexane were poured in for extraction of methyl esters. After thorough shaking and settling the hexane extract was filtered off and used for chromatographic analysis. Research results. 13 fatty acids, 1 of which is unidentified, were found in the fruit bodies of Agaricus bisporus. Among the identified fatty acids, 6 saturated and 6 unsaturated acids were identified. As a result of the conducted research, it was established that among all the detected fatty acids, unsaturated acid - linoleic acid (75.50%) prevailed in terms of content. Regarding saturated acids, palmitic acid (13.85%) was present in a fairly large amount. It should be noted that the information we received correlates with the data of other scientists. Unidentified, arachinic and myristic acid were contained in small amounts. Unsaturated fatty acids (80.75%) predominated in the fruit bodies of Agaricus bisporus. During the experiment, it was established that the amount of saturated fatty acids was 4 times less than the amount of unsaturated acids. The amount of unidentified acids was 0.10%. Conclusions. Thus, the study of the fatty acid composition of Agaricus bisporus fruit bodies was carried out. In the course of the experiment, the dominance of the sum of unsaturated fatty acids was established. The obtained data deepen the knowledge about the chemical composition of Agaricus bisporus, which can be used both in pharmacy and in nutritiology. Keywords: Agaricus bisporus, fatty acids, gas chromatography